2011 International Conference on Management and Service Science 2011
DOI: 10.1109/icmss.2011.5999199
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Iran Stock Market Indices Using Recurrence Plots

Abstract: Market data analysis in Iran stock market has been considered in this paper. The experimental data are the shares prices from Iran stock market covering a period of 5 years which is long enough to take the properties such as non-stationary of the market into account. The analysis tools are the time series analysis methods such as power spectral density analysis, time series histogram plot, and the recurrence plots. Nonlinear analysis over the shares' prices time series' for some companies such as Iran Khodro C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…RP and used it to detect nonlinearities and chaotic dynamics in experimental signals in physics. The RP technique has been used recently to identify structural changes and hidden patterns in data or detect similarities in patterns across the time series in many fields, such as economics [26], physiology [27], and energy markets [27]. In this paper, the RP technique will be applied to analyze the predictability of the wind time series.…”
Section: Methodsmentioning
confidence: 99%
“…RP and used it to detect nonlinearities and chaotic dynamics in experimental signals in physics. The RP technique has been used recently to identify structural changes and hidden patterns in data or detect similarities in patterns across the time series in many fields, such as economics [26], physiology [27], and energy markets [27]. In this paper, the RP technique will be applied to analyze the predictability of the wind time series.…”
Section: Methodsmentioning
confidence: 99%
“…It is shown that during these events stock markets exhibit a distinctive behavior that is characterized by temporary decreases in the fraction of recurrence points contained in diagonal and vertical structures. Similarly, Bigdeli et al [4] analyzed the dynamical properties of Iranian stock prices using recurrence quantification analysis along with other methods. They found evidences of seasonality and nonstationarity in the data analyzed , and discussed the use of the measure "laminarity" to identify market bubbles.…”
Section: Literature Reviewmentioning
confidence: 99%